Relevance of Accounting Information: Audit Quality and Earnings Management as Moderating Variable - Stephania Eryn Liemmuel; Rizky Eriandani (Jurnal Dinamika Akuntansi, 2022)
Purposes: This study investigates whether audit quality and earnings management moderate the effect of accounting information on market prices.Methods: This study consisted of a sample of 1525 go public firms on Indonesia Stock Exchange from 2016 – to 2020, except financial sector. Proxies of accounting information are earnings, book value, and operating cash flow. Audit quality is measured by auditor type and audit opinion. This study uses purposive sampling and testing moderated regression analysis.Results: The results indicate that accounting information - earnings; book value, and operating cash flow have a positive effect on stock market prices. Furthermore, the type of auditor and audit opinion strengthen the correlation between earnings and stock prices. However, it does not moderate the effect of book value and operating cash flow on stock prices. Furthermore, earnings management weakens the effect of earnings on stock prices. However, earnings management does not moderate the correlation of book value of equity and operating cash flows with stock prices.Novelty: This study enriched the literature on value relevance which is influenced by other factors such as audit quality and Earnings Management. It is hoped that further researchers can expand their research by examining other accounting information and other factors that can be used as a basis for investor considerations for investment decisions such as corporate governance or others